A Comparative Genome-Wide Analysis of the R2R3-MYB Gene Family Among Four Gossypium Species and Their Sequence Variation and Association With Fiber Quality Traits in an Interspecific G. hirsutum × G. barbadense Population - Wang, Nuohan; Ma, Qiang; Ma, Jianjiang; Pei, Wenfeng; Liu, Guoyuan; Cui, Yupeng; Wu, Man; Zang, Xinshan; Zhang, Jinfa; Yu, Shuxun; Ma, Lingjian; Yu, Jiwen (Frontiers in Genetics, 2019)
Cotton (Gossypium spp.) is the most important natural fiber crop in the world. The R2R3-MYB gene family is a large gene family involved in many plant functions including cotton fiber development. Although previous studies have reported its phylogenetic relationships, gene structures, and expression patterns in tetraploid G. hirsutum and diploid G. raimondii, little is known about the sequence variation of the members between G. hirsutum and G. barbadense and their involvement in the natural quantitative variation in fiber quality and yield. In this study, a comprehensive genome-wide comparative analysis was performed among the four Gossypium species using whole genome sequences, i.e., tetraploid G. hirsutum (AD1) and G. barbadense (AD2) as well as their likely ancestral diploid extants G. raimondii (D5) and G. arboreum (A2), leading to the identification of 406, 393, 216, and 213 R2R3-MYB genes, respectively. To elucidate whether the R2R3-MYB genes are genetically associated with fiber quality traits, 86 R2R3-MYB genes were co-localized with quantitative trait loci (QTL) hotspots for fiber quality and yield, including 42 genes localized within the fiber length QTL hotspots, in interspecific G. hirsutum × G. barbadense populations. There were 20 interspecific nonsynonymous single-nucleotide polymorphism (SNP) sites between the two tetraploid cultivated species, of which 16 developed from 11 R2R3-MYB genes were significantly correlated with fiber quality and yield in a backcross inbred population (BIL) of G. hirsutum × G. barbadense in at least one of the four field tests. Taken together, these results indicate that the sequence variation in these 11 R2R3-MYB genes is associated with the natural variation (i.e., QTL) in fiber quality and yield. Moreover, the functional SNPs of five R2R3-MYB allele pairs from the AD1 and AD2 genomes were significantly correlated with the gene expression related to fiber quality in fiber development. The results will be useful in further elucidating the role of the R2R3-MYB genes during fiber development.